Design and FE analysis of chassis for solar powered vehicle. (2022) - Patel, Deep; Jasani, Vivek; Shah, Dhaval; Lakdawala, Absar
Abstract: The chassis is one of the most important structures of an automobile which accommodates many parts of the vehicle. Many types of forces are acting on the vehicle during running conditions which results in crack initiation and deformation in the various members of the chassis. This research paper provides a detailed description of the general design considerations, static analysis of solar-powered vehicle chassis. Different analyses like front impact, rear impact, side impact, bump analysis and torsional analysis are carried out to determine the areas of maximum stress generation. Two steel grades AISI 4130 and AISI 1018 are compared based on high strength to weight ratio, cost and manufacturability. The excellent chassis is designed based on the results of analysis for all the possible loads in various directions. The 3D solid CAD model of the chassis is prepared using SolidWorks. The static structural analysis of the roll cage is performed using ANSYS. It has been found that the factor of safety obtained for AISI 4130 is 116.43% more than that of AISI 1018.